Rapid Tooling Guidelines For Sand Casting - Wang, Wanlong; Stoll, Henry W.; Conley, James G.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Rapid Tooling Guidelines For Sand Casting is a comprehensive tool for those who wish to improve their products and realization processes by better understanding the decisions involved in selecting sand casting tooling path and, in turn, improving cost, quality and delivery. Based on extensive research into the relationship between part geometry, production quantity, tool materials, tooling fabrication method and production tolerances, the book presents a variety of decision methods and case studies that address topics such as: Identification of part geometries that are suitable for sand casting Evaluation of error sources and alternative methods for creating tooling Optimal tooling path selection and its effects on production dimensional accuracy Analysis of tooling related costs and lead times Rapid Tooling Guidelines For Sand Casting is a useful resource for engineers, researchers and students in the sand casting and the rapid tooling industry.
Sand Casting Processes -- Tool Design and Construction for Sand Casting -- Fast Freeform Fabrication Methods and Processes -- Rapid Tooling Processes -- Sand Casting Dimensional Control -- Evaluating Tooling Alternatives -- Tooling Alternative Selection Case Studies.
Keywords: Engineering; Materials; Machinery; Engineering; Manufacturing, Machines, Tools; Control; Continuum Mechanics and Mechanics of Materials